(untitled) (Journal of Hama University, 2021)
This study aimed at identifying the impact of Automatic Teller Machine (ATM) service quality on customer satisfaction amongst of public and private bank branches in the city of Hama, it also aimed to identifying the difference in assessing both of ATM service quality and customer satisfaction among these two sectors. In order to achieve the research objectives, a questionnaire was designed consisting of field covering dimensions of an ATM service quality scale developed by this study. In addition to a field specific to customer satisfaction. The study adopted the descriptive method, where few hypotheses are developed and tested using statistical tests in the SPSS 20 package. The study results show that ATM service quality positively affects customer satisfaction in both the case of public banks and that of private ones. Furthermore, ATM service quality seems to be moderate in both cases, but its higher in the case of private banks. Likewise, the customer satisfaction is moderate in both cases, but its higher in the private banks.